Análisis y propuesta para la gestión del talento humano del Sindicato Provincial de Choferes de Loja - Bustamante Correa, Ludy Antonieta (2016)
A few years ago , human resource is called cataloging man as an instrument in the chain of production, but the replaceable believed, but now it is considered as the main and essential capital to reach the success of the organization , such term has evolved human talent. Also the task of the organizations was properly manage human talent in all its phases : recruiting , training and developing qualified personnel , competitive forming working groups able to mold and adapt to constant change. Currently small and medium-sized enterprises of our country have a development that the government increasingly seeks to promote and support the economic sector with reduced amounts of investment , organization, management and human resources management consequently , low levels of profitability and productivity but to this context all Talent in recent times has been established as the most prevalent problem in the private sector where there is a notorious lack of application of appropriate management techniques associated and management structure organizational . Also one of the limitations of the companies and institutions of our country is the way how to direct and coordinate activities with the staff , as the unknowns of techniques and methods do not allow companies to have a coordinated staff activities , trained and stable in the workplace , performing personnel management today an empirical and uncoordinated way , which does not allow the harmonious development of their activities which is why the fundamental purpose is to contribute to contribute to the " Provincial Union of Drivers Loja " to which it may give importance to human talent because when the term human Resource use is cataloging the person as a means , without considering that this is the principal, which possesses skills and characteristics that give it life , movement and action to any organization . Within the Business Administration has found that the Provincial Union Drivers of Loja demonstrates the inadequate implementation of the phases of personnel administration has generated low productivity , slow advancement and exploitation of the potential of staff and merely creating a work climate conducive organizational development , as the institution is not established due structural and functional organization , or are clearly finds hierarchical levels , except the Director level , but this by sea to the creation of the union 63 years ago was as a conductor q then guild name was attributed union , and with the passing of the years it has grown both in its membership and staff. From what I can mention in diagnosing the Provincial Union Drivers of Loja not have a department or Head of Talent that focuses on pursuing the functional and personal goals , being the main problem the lack of relationship between employees , training and development, as which has limited the progress and implementation of activities by some workers , so we can also mention the non-implementation of the evaluation process of the performance of employees and that the same has never been done . It is therefore proposed to increase the staff of employees a head of human talent in order to harmonize the activities of the institution as well as improving the recruitment staff Loja Provincial Drivers Union and even a service provided by the institution " Driving School " and is an autonomous and structure based on the laws of the National Transit Agency legal body . Union belongs to its employees and therefore benefiting from this proposal. Moreover a performance evaluation is proposed to improve the performance of employees and implement a plan that will enhance your motivational abilities and skills when performing their work activities